2005
DOI: 10.1038/sj.npp.1300695
|View full text |Cite
|
Sign up to set email alerts
|

Blood Levels of the Endocannabinoid Anandamide are Increased in Anorexia Nervosa and in Binge-Eating Disorder, but not in Bulimia Nervosa

Abstract: The endocannabinoid system, consisting of two cannabinoid receptors (CB 1 and CB 2 ) and the endogenous ligands anandamide (arachidonoylethanolamide (AEA)) and 2-arachidonoylglycerol (2-AG), has been shown to control food intake in both animals and humans, modulating either rewarding or quantitative aspects of the eating behavior. Moreover, hypothalamic endocannabinoids seem to be part of neural circuitry involved in the modulating effects of leptin on energy homeostasis. Therefore, alterations of the endocann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
2
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(174 citation statements)
references
References 27 publications
8
152
2
12
Order By: Relevance
“…In this direction, Endogenous cannabinoids in the brain and peripheral tissues I Matias et al data from our laboratory indicate that the blood levels of endocannabinoids in anorexic women are significantly higher than in healthy women, and inversely correlated with blood leptin levels. 35 Furthermore, obese women with binge eating disorder, despite the very high levels of leptin, also possess higher blood endocannabinoid levels, which in this case are positively correlated with body fat mass, thus suggesting that one type of control on the endocannabinoid system may prevail over another during some eating disorders. 35 Indeed, the picture of a general hyperactivity of the endocannabinoid system during obesity, at both the central and peripheral levels, is emerging from recent studies.…”
Section: Discussionmentioning
confidence: 87%
“…In this direction, Endogenous cannabinoids in the brain and peripheral tissues I Matias et al data from our laboratory indicate that the blood levels of endocannabinoids in anorexic women are significantly higher than in healthy women, and inversely correlated with blood leptin levels. 35 Furthermore, obese women with binge eating disorder, despite the very high levels of leptin, also possess higher blood endocannabinoid levels, which in this case are positively correlated with body fat mass, thus suggesting that one type of control on the endocannabinoid system may prevail over another during some eating disorders. 35 Indeed, the picture of a general hyperactivity of the endocannabinoid system during obesity, at both the central and peripheral levels, is emerging from recent studies.…”
Section: Discussionmentioning
confidence: 87%
“…36,37 Physiologically, this can promote feelings of being unable to control one's response to eating and food. 38,39 Subsequently, this may increase UE, EE and, in some populations, decrease CR. Clearly, more research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…S1B). Quantitative analysis using liquid chromatography-multiple reaction monitoring (LC-MRM) measurements revealed that only 23.6 ± 4.8% (n = 6) of the exogenously applied dose of lipophilic AEA reached the lungs via the tubes of the perfusion system of the IPL; these data indicate that AEA evoked pulmonary vasoconstriction at concentrations that have been measured in the human blood (13,14). The effect of AEA was specific because no response was observed upon perfusion with the solvent ethanol ( Fig.…”
Section: Resultsmentioning
confidence: 87%